The Fragility of Coerced Faith: Deconstructing the Constitutional Court’s Ratio Decidendi via the Aḥmadiyyah Exegesis of Qurʾān 2:256 - Masgun Arifin; Ahmad Nabilul Maram (Al-Ulum, 2026)
This article challenges the legal-theological logic underpinning the Indonesian Constitutional Court (Mahkamah Konstitusi or MK) Decision No. 140/PUU-VII/2009, which upheld the Blasphemy Law on the grounds of maintaining "public order" and "religious purity" (ḥifẓ al-dīn). While existing scholarship predominantly critiques this decision through secular human rights frameworks, this study employs a hermeneutic dialectic method to confront the Court’s reasoning with an internal Islamic counter-narrative: the Aḥmadiyyah exegesis (tafsīr) of Qurʾān 2:256. The analysis reveals a fundamental epistemological divergence. The MK operates on a paradigm of "doctrinal fragility," assuming that religious truth requires coercive state protection to survive deviations. Conversely, the minority exegesis posits that because Truth (al-rushd) is ontologically distinct from Error (al-ghayy), coercion is logically redundant and theologically invalid. Empirical evidence from the Cikeusik and Sintang incidents further demonstrates that the state’s restrictive approach to ḥifẓ al-dīn creates a "feedback loop" of structural violence, where the legal designation of deviance legitimizes vigilante aggression, thereby violating ḥifẓ al-nafs (protection of life). By deconstructing the classical doctrine of abrogation (naskh) and redefining fitnah (disorder) as persecution rather than difference, this article argues for a systemic reconstruction of Maqāṣid al-Sharīʿah. It concludes that genuine public order in a pluralist state cannot be achieved through the policing of orthodoxy, but only through the recognition of conscience (ḥurriyyat al-iʿtiqād) as a prerequisite for social peace.